Genetic Diversity and Selection of MHC I-UAA in Clariid Catfish from Thailand: Implications for Breeding and Conservation - Ton Huu Duc Nguyen; Piangjai Chalermwong; Chananya Patta; Wattanawan Jaito; Worapong Singchat; Thitipong Panthum; Trifan Budi; Kednapat Sriphairoj; Sittichai Hatachote; Prapansak Srisapoome; Narongrit Muangmai; Darren K. Griffin; et al. (Genes, 2025)
polymorphism and disease resistance is debated, studies suggest associations with pathogen survival, indicating future implications for aquaculture breeding and conservation, particularly in marker-assisted selection for broodstock management in Thailand.
Keywords: Aquaculture disease management and microbiota; T-cell and B-cell Immunology; Immune Cell Function and Interaction